Additives Aid Switch to Protect the Photodegradation of Plastics in Outdoor Construction - Mohammed, Salam A.; Yusop, Rahimi M.; Mohammed, Mohammed Abdulsattar; Mohammed, Rasheed Abed; Ahmed, Dina S.; Ahmed, Ahmed Abdulrazaq; Ahmed, Ahmed Abdulelah; Ali, Basheer; Yousif, Emad (Al-Nahrain Journal for Engineering Sciences, 2019)
Poly(vinyl chloride) photodecomposition films that contains melamine Schiff base (0.5% by weight) as photostabilizers upon preservation with an ultraviolet light (UV) was investigated. The photodecomposition rate constant was reduced significantly in existence of melamine Schiff base compared to PVC (blank). The Schiff base 1 was found to most effective additive in PVC photostabilization films. Photodecomposition rate content for PVC films containing Schiff base 1 was found to be 5 × 10-3 sec-1 compared to 8.7 × 10-3 sec-1 for blank film. Ultraviolet radiation aging behaviors of PVC films were studied through leaching test by measuring the degree of migration. The surface morphology of PVC films was inspected by scanning electron microscope.